Noninvasive assessment of hepatic iron overload in pediatric patients with β-thalassemia major using T2* magnetic resonance imaging and shear wave elastography - Mona Elkalioubie; Yasmeen Selim; Wessam Elzayat (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Secondary hemochromatosis ensues as a result of life long blood transfusions with possibly life-threatening hepatic iron overload in pediatric patients with β-thalassemia. Careful monitoring and follow-up is required to modify chelation therapy. The study aims to examine the correlation between liver iron concentration (LIC) by MRI T2*, shear wave elastography (SWE) and serum ferritin to detect clinically significant liver fibrosis. Results Iron accumulation was detected in all patients who were categorized as three groups according to MRI T2*: mild in 18 (40%), moderate in 18 (40%), and severe in nine patients (20%). Serum ferritin levels (SFL) were elevated in all patients (1044–4418 ng/ml.) A statistically significant difference between the three groups was found as regard to the mean SWE values only. There was a strong agreement between SWE and T2*MRI (ICC = 0.8443) and excellent agreement between SFL and T2*MRI method (ICC = 0.9388). There was a moderate negative correlation between SWE and T2* MRI (R =  − 0.6611, p = 0.07 NS), a moderate positive correlation between SWE and SFL (R = 0.6406, p = 0.08 NS), and a moderate negative correlation between SFL and T2*MRI (R =  − 0.6905, p = 0.059, NS). ROC analysis for SWE to predict moderate and severe fibrosis as graded by the results of MRI T2* showed an area under the curve of 0.833 (p = 0.068). Optimal cut-off values were 10.35 kilopascals (specificity = 100%, sensitivity 66.7%) and 9.8 kilopascals (specificity = 80%, sensitivity 66.7%). ROC analysis for SFL to predict moderate and severe fibrosis as graded by the results of MRI T2* showed an area under the curve of 0.733 (p = 0.2). Optimal cut-off value was 2351 (specificity = 80%, sensitivity 66.7%). Conclusion Shear wave elastography is a useful technique in monitoring iron hepatic overload in children affected by β-thalassemia with a moderate negative correlation and strong agreement with T2*-weighted MRI. An optimal cut-off value of SWE can be used to predict adverse effects of moderate and severe liver iron overload in these patients, and this can be used as an adjunct technique to T2*-weighted MRI in the follow-up of chelation therapy.